2011
DOI: 10.18061/dsq.v31i4.1718
|View full text |Cite
|
Sign up to set email alerts
|

Parents and Course Leaders' Experiences of the ComAlong Augmentative and Alternative Communication Early Intervention Course

Abstract: <p>Keywords</p><p>early intervention, parental education, communication development, augmentative and alternative communication (AAC), parents' experiences</p><p>Abstract</p><p>The aim of this study was to evaluate parents and course leaders' experiences of the ComAlong early intervention course; a parental course about communication, communication development, play, responsive communication strategies and augmentative and alternative communication (AAC). ComAlong targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…However, informal conversation was by far the most common mode of instruction as reported by the SLPs in this study supporting earlier findings from other study populations [73]. Programmes aimed at empowering and enhancing the communicative knowledge and skills of parents have been developed for a general population and some specifically modified for persons with Rett syndrome [38,68,[80][81][82]. Use of programmes or other systematic instructions has been promising in increasing the implementation of aided communication in other populations [83].…”
Section: Slp-estimated Outcomesupporting
confidence: 86%
“…However, informal conversation was by far the most common mode of instruction as reported by the SLPs in this study supporting earlier findings from other study populations [73]. Programmes aimed at empowering and enhancing the communicative knowledge and skills of parents have been developed for a general population and some specifically modified for persons with Rett syndrome [38,68,[80][81][82]. Use of programmes or other systematic instructions has been promising in increasing the implementation of aided communication in other populations [83].…”
Section: Slp-estimated Outcomesupporting
confidence: 86%
“…All 22 participants were however included in the quantitative analysis regarding the global rating scale that was included in both the forms. This procedure enabled us to compare the current results with the data reported in Ferm et al (2011) in order to find out whether the responses of the participants in this study (parents of children with PIMD) differed from those of the ComAlong course's broader target group.…”
Section: Methodsmentioning
confidence: 99%
“…In between sessions, the participants are given homework assignments to help enhance their learning and reflection and to support the application of the knowledge they have acquired in their communication with their child in the home environment (Broberg et al 2012, Jonsson et al 2011. Ferm et al (2011) examined parents' and course leaders' experiences of the ComAlong course when held for a broad target group. The results showed that parents generally found the course to be a positive experience and that they also experienced positive changes in their own communication as well as that of their child (Ferm et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specialist level, such as Child and Youth Habilitation services or CAP, receive referrals from CHC in cases of suspected ASD, ADHD, Intellectual Disability or ESSENCE concept symptoms (Gillberg, 2010;Spjut Jansson et al, 2016). After investigation, the specialist-level intervention usually starts with pa-rental psycho-education and counselling in communication skills and be-haviour modification (Ferm, 2011). Parental contributions focusing on communicating with the child, implemented at an early age and contin-ued over a long period of time, together with the preschool teacher, seems to be the most effective intervention (Carr et al, 1994;Devescovi et al, 2016;Hejlskov Elvén, 2009;Jones et al, 2010;Spjut Jansson et al, 2016).…”
Section: Early Interventions In Healthcarementioning
confidence: 99%